2005
DOI: 10.1021/jo0515677
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocenylketene and Ferrocenyl-1,2-bisketenes:  Direct Observation and Reactivity Measurements

Abstract: [Structure: see text]. Ferrocenylketene (1) is calculated to be destabilized by 1.6 kcal/mol relative to phenylketene (10) by B3LYP isodesmic comparison to the corresponding alkenes. Ketene 1 generated by Wolff rearrangement in CH3CN is identified by the IR band at 2119 cm(-1) and has a rate constant for reaction with n-BuNH2 less than that for 10 by a factor of 5. 1,2-Bisferrocenyl-1,2-bisketene 18 and 1-ferrocenyl-2-trimethylsilyl-1,2-bisketene 21 were prepared by photochemical ring opening of the correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…However, the solid-state structures of 12 and 13 are actually most closely related to the one-directional [Cd(TeC 6 H 2 Me 3 ) 2 ] 1 and [Ag 10 10 ] 1 complexes. [21] Although the coordination polymers 12 and 13 do not contain any phosphine ligands, the structures can be described in a manner similar to that of 20c] with the shortest bond length to the linear silver center.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the solid-state structures of 12 and 13 are actually most closely related to the one-directional [Cd(TeC 6 H 2 Me 3 ) 2 ] 1 and [Ag 10 10 ] 1 complexes. [21] Although the coordination polymers 12 and 13 do not contain any phosphine ligands, the structures can be described in a manner similar to that of 20c] with the shortest bond length to the linear silver center.…”
Section: Resultsmentioning
confidence: 99%
“…Ferrocenoyl chloride was first prepared in situ through the addition of oxalyl chloride to a stirred suspension of ferrocene carboxylic acid in CH 2 Cl 2 at RT. [10] The reaction with NEt 3 / 2-bromoethanol generated 2-bromoethylferrocenylcarboxy- [7g] However, the chalcogenols [FcC(O)OCH 2 CH 2 EH] (2a E = S, 3a E = Se) could be prepared through the addition of tetrabutylammonium fluoride hydrate (TBAF) to a wellstirred solution of 1 with EA C H T U N G T R E N N U N G (SiMe 3 ) 2 in THF at À10 8C. [11] Tetrabutylammonium bromide was removed through precipitation with heptane and filtration of the reaction mixtures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 1,2-Bisferrocenyl-1,2-bisketene 4 was also prepared as a transient intermediate by photochemical ring opening of the corresponding cyclobutenedione 3, and 4 underwent rapid ring closure back to the cyclobutenedione with a rate constant 67 times greater than that for the corresponding 1,2-diphenyl-1,2-bisketene (Scheme 2). 3 Thus the computational and experimental results indicated that ferrocenylketenes are less stabilized and more reactive than phenylketenes. This is consistent with the known destabilizing effects of electron donating substituents on ketenes, 1d and the strong electron donating ability of the ferrocenyl group.…”
Section: Introductionmentioning
confidence: 99%
“…Ferrocenylketene 1 was generated by Wolff rearrangement in CH 3 CN and was directly observed by UV and IR spectroscopy as a short-lived and reactive intermediate in solution. 3 Ferrocenylketene was identified by the characteristic IR band at 2119 cm -1 , and was found to have a rate constant for reaction with n-BuNH 2 forming the corresponding amide less than that for phenylketene by a factor of 5 (Scheme 2). 3 1,2-Bisferrocenyl-1,2-bisketene 4 was also prepared as a transient intermediate by photochemical ring opening of the corresponding cyclobutenedione 3, and 4 underwent rapid ring closure back to the cyclobutenedione with a rate constant 67 times greater than that for the corresponding 1,2-diphenyl-1,2-bisketene (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%